EDUCATIONAL VALUES IN 'HIKAYAT HANG TUAH' MALAY FOLKTALE - Agik Nur Efendi; M. Zainal Muttaqien (UIN Raden Mas Said Surakarta, 2017)
Globalization era has affected in the changes of Indonesian people’s values. The changes has gradually transformed norms in society. Therefore, it is urgent to educate character values to the new generations. It can—among others—be conducted by learning from Hikayat Hang Tuah, a classic Malay literary work which contains values relevant to both daily lives and character education. This article is aimed at describing some values included in Hikayat Hang Tuah. The character education contained by the story is considered having relevance to the program established by Ministry of Education and Culture nowadays. The findings show that Hikayat Hang Tuah loads different educational values ranging from the aspects of religion, nationalism, integrity, autonomy, to cooperation. Hopefully, this article can give contributions to the development of students’ character education from Hikayat Hang Tuah story.